Plasma fibrinogen and blood platelet counts are associated with response to neoadjuvant therapy in esophageal cancer. (March 2015) - Ilhan-Mutlu, Aysegül; Starlinger, Patrick; Perkmann, Thomas; Schoppmann, Sebastian F; Preusser, Matthias; Birner, Peter
Aim: To investigate coagulatory factors in predicting response to neoadjuvant therapy (NeoTr) in esophageal cancer (EC).Methods: We investigated the relevance of coagulatory factors in 84 EC patients (56 adenocarcinomas, 28 squamous cell cancer) who received NeoTr. Plasma fibrinogen (PFR), peripheral blood platelet counts (PBPC) and C-reactive protein (CRP) were determined before NeoTr. Response was classified as tumor regression grades.Results: Patients with good response to NeoTr had significantly higher PFR (p = 0.006), CRP (p = 0.002) and PBPC levels (p = 0.034) when compared with others. Only, PFR remained an independent factor influencing tumor regression (p = 0.0064, coefficient of regression: -0.003). No association with survival was observed.Conclusion: PFR and to a lesser extent PBPC and CRP might be considered as a predictive marker for the response to NeoTr in EC.